A novel configuration for single-crystal superalloy hollow blade manufacturing based on shell/core integral mold - Binqiang Wang; Zhexu Li; Kun Bu; Zhongliang Lu; Jiawei Zhang; Sheng Mou; Shengjie Ren; Haoyu Zhao (Journal of Materials Research and Technology)
Shell/core integral mold fabricated by additive manufacturing possess high shell/core bonding strength, which is promising to improve the dimensional accuracy and integrity of single-crystal (SX) hollow blade while improving the manufacturing efficiency. In this study, a novel inverted configuration of SX hollow blade was proposed based on shell/core integral mold, resulting in a 55 mm reduction of platform height compared to the upright configuration. Temperature field, microstructure, stress and displacement field were simulated using finite element method, showcasing the superiority of the inverted blade. Compared to the upright blade, the inverted blade exhibited nearly flat liquidus isotherm, of which undercooling was decreased while thermal gradient of platform was increased, leading to the successful attainment of a SX. Stress and displacement distribution for two configurations of SX hollow blade were extremely similar under constraints removal condition, therefore, blade configuration doesn't greatly affect stress and displacement field of SX hollow blade. The formability and integrity of SX hollow blade, [001] orientation controlled by substrate stimulating technique were verified by directional solidification experiment. This work provides a new strategy for SX hollow blade manufacturing.